Method for pulverizing sulfur compound, method for pulverizing solid electrolyte, method for producing solid electrolyte, and solid electrolyte

By controlling the relationship between particle size and ionic conductivity during the pulverization process and employing a wet pulverization method, the problem of decreased ionic conductivity after pulverization of solid electrolytes in existing technologies has been solved, resulting in solid electrolyte powder with high ionic conductivity, suitable for solid-state batteries of lithium-ion batteries.

CN119365938APending Publication Date: 2025-01-24MITSUI MINING & SMELTING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380047142.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-08
Filing Date
2023-06-29
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When existing pulverization methods pulverize solid electrolytes, the ionic conductivity decreases compared to before pulverization, which fails to fully utilize the characteristics of solid-state batteries.

Method used

By controlling the relationship between particle size and ionic conductivity during the pulverization process to satisfy specific formulas (D2/D1<0.49 and A/B<3.6×10-3), a wet pulverization method is adopted, using a media mill and organic solvent, and controlling the diameter and time of the pulverization media to ensure that the particle size and ionic conductivity of the solid electrolyte are within a specific range.

Benefits of technology

It improves the ionic conductivity of solid electrolytes, ensuring that the conductivity and particle size meet the requirements after pulverization, making it suitable for solid-state batteries in lithium-ion batteries, thereby enhancing battery safety and energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187349510000231
    Figure BDA0005187349510000231
  • Figure FDA0005187349500000041
    Figure FDA0005187349500000041
Patent Text Reader

Abstract

Provided is a method for pulverizing a sulfur compound, the method satisfying the relationship represented by formula (1). D2 / D1 < lt >; 0.49 (1) (In the formula, D1 represents the median diameter of the unpulverized sulfur compound when the pulverizing method has only one pulverizing step. In addition, when the pulverization method has two or more pulverization steps, D1 represents the median diameter of the sulfur compound before the pulverization step is performed in any of the pulverization steps. And D2 represents the median diameter of the crushed sulfur compound when the crushing method has only one crushing step. And D2 represents the median diameter of the sulfur compound after the grinding step is performed in any of the grinding steps when the grinding method has two or more grinding steps).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for pulverizing a sulfur compound, a method for pulverizing a solid electrolyte, a method for producing a solid electrolyte, and a solid electrolyte. Background Art

[0002] Currently, many lithium-ion secondary batteries use electrolytes containing flammable organic solvents. In contrast, solid-state batteries that use solid electrolytes instead of electrolytes and do not contain flammable organic solvents are expected to be put into practical use as batteries that combine safety with high energy density.

[0003] In order to realize solid-state batteries, solid electrolytes are being actively developed. Solid electrolytes generally have lower ion conductivity than organic electrolytes, making them difficult to put into practical use. Solid electrolytes can be obtained by mixing and calcining specified raw materials to obtain raw material powders of crystalline solid electrolytes, and then crushing them using a bead mill or the like (Patent Documents 1 to 3).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2009-211950

[0007] Patent Document 2: Japanese Patent Application Publication No. 2010-140893

[0008] Patent Document 3: Japanese Patent Application Publication No. 2008-004459 Summary of the invention

[0009] However, when a solid electrolyte is pulverized using a conventional pulverization method, the ion conductivity decreases compared to before pulverization, and there is a problem that the characteristics as a solid-state battery cannot be fully exerted.

[0010] Therefore, the technical problem of the present invention is to provide a solid electrolyte powder having excellent ion conductivity.

[0011] The present inventors conducted intensive research to solve the above problems and found a pulverization method by which the particle sizes of the solid electrolyte before and after pulverization satisfy a predetermined relationship, thereby obtaining a target solid electrolyte powder.

[0012] That is, the present invention provides a method for pulverizing a sulfur compound, which is a method for pulverizing a sulfur compound.

[0013] The method satisfies the relationship shown in the following formula (1).

[0014] D2 / D1<0.49 (1)

[0015] (wherein, D1 represents the median particle size of the un-crushed sulfur compound when the pulverization method has only one pulverization step. In addition, D1 represents the median particle size of the sulfur compound before the pulverization step is performed in any pulverization step when the pulverization method has two or more pulverization steps.

[0016] D2 represents the median particle size of the sulfur compound after the pulverization when the pulverization method has only one pulverization step. D2 represents the median particle size of the sulfur compound after the pulverization step is performed in any of the pulverization steps when the pulverization method has two or more pulverization steps.

[0017] In addition, the present invention provides a method for pulverizing a sulfur compound, which is a method for pulverizing a sulfur compound.

[0018] The method satisfies the relationship shown in the following formula (2).

[0019] A / B<3.6×10 -3 (2)

[0020] (wherein, A (S / cm) represents the difference between the ionic conductivity (S / cm) of the sulfur compound after the pulverization step and the ionic conductivity (S / cm) of the unpulverized sulfur compound when the pulverization method has only one pulverization step. In addition, A (S / cm) represents the difference between the ionic conductivity of the sulfur compound before any pulverization step and the ionic conductivity of the sulfur compound after the arbitrary pulverization step when the pulverization method has two or more pulverization steps.

[0021] When the pulverization method has only one pulverization step, B (μm) represents the difference between the median particle size (μm) of the unpulverized sulfur compound and the median particle size (μm) of the sulfur compound after the pulverization step. In addition, when the pulverization method has two or more pulverization steps, B (μm) represents the difference between the median particle size (μm) of the sulfur compound before the arbitrary pulverization step and the median particle size (μm) of the sulfur compound after the arbitrary pulverization step.)

[0022] Furthermore, the present invention provides a method for pulverizing a solid electrolyte, which comprises:

[0023] a preparation step of preparing a solid electrolyte; and

[0024] a pulverizing step of pulverizing the solid electrolyte,

[0025] The pulverization step satisfies the relationship shown in the following formula (3).

[0026] D4 / D3<0.49 (3)

[0027] (wherein, D3 represents the median particle size of the un-crushed solid electrolyte when there is only one pulverization step. In addition, D3 represents the median particle size of the solid electrolyte before the pulverization step is performed in any pulverization step when there are two or more pulverization steps.

[0028] D4 represents the median particle size of the solid electrolyte after the pulverization when there is only one pulverization step. D4 represents the median particle size of the solid electrolyte after the pulverization step is performed in any of the pulverization steps when there are two or more pulverization steps.

[0029] In addition, the present invention provides a solid electrolyte pulverization method, which has the following characteristics:

[0030] a preparation step of preparing a solid electrolyte; and

[0031] a pulverizing step of pulverizing the solid electrolyte,

[0032] The pulverization step satisfies the relationship expressed by the following formula (4).

[0033] C / D<3.6×10 -3 (4)

[0034] (Wherein, C (S / cm) represents the difference between the ionic conductivity (S / cm) of the solid electrolyte after the pulverization step and the ionic conductivity (S / cm) of the unpulverized solid electrolyte when the pulverization step is performed only once. In addition, C (S / cm) represents the difference between the ionic conductivity (S / cm) of the solid electrolyte before any pulverization step and the ionic conductivity (S / cm) of the solid electrolyte after any pulverization step when the pulverization step is performed twice or more.

[0035] D (μm) indicates the difference between the median particle size (μm) of the un-crushed solid electrolyte and the median particle size (μm) of the solid electrolyte after the crushing step when the crushing method has only one crushing step. In addition, D (μm) indicates the difference between the median particle size (μm) of the solid electrolyte before any crushing step and the median particle size (μm) of the solid electrolyte after the crushing step when the crushing method has two or more crushing steps.)

[0036] Furthermore, the present invention provides a method for producing a solid electrolyte, the method comprising the steps of pulverizing a solid electrolyte mother powder,

[0037] The pulverization step satisfies the relationship shown in the following formula (5).

[0038] D6 / D5<0.49 (5)

[0039] (Wherein, D5 represents the median particle size of the mother powder when there is only one pulverization step. In addition, D5 represents the median particle size of the solid electrolyte before any pulverization step when there are two or more pulverization steps.

[0040] D6 represents the median particle size of the solid electrolyte after the pulverization step when there is only one pulverization step. D6 represents the median particle size of the solid electrolyte after any pulverization step when there are two or more pulverization steps.

[0041] In addition, the present invention provides a method for producing a solid electrolyte, the method comprising the steps of pulverizing a solid electrolyte mother powder,

[0042] The pulverization step satisfies the relationship shown in the following formula (6).

[0043] E / F<3.6×10 -3 (6)

[0044] (Wherein, E (S / cm) represents the difference between the ionic conductivity (S / cm) of the solid electrolyte after the pulverization step and the ionic conductivity (S / cm) of the unpulverized solid electrolyte when the pulverization step is performed only once. In addition, E (S / cm) represents the difference between the ionic conductivity (S / cm) of the solid electrolyte before any pulverization step and the ionic conductivity (S / cm) of the solid electrolyte after any pulverization step when the pulverization step is performed twice or more.

[0045] F (μm) represents the difference between the median particle size (μm) of the un-crushed solid electrolyte and the median particle size (μm) of the solid electrolyte after the pulverization step when there is only one pulverization step. In addition, F (μm) represents the difference between the median particle size (μm) of the solid electrolyte before any pulverization step and the median particle size (μm) of the solid electrolyte after the pulverization step when there are two or more pulverization steps.)

[0046] Furthermore, the present invention provides a solid electrolyte, wherein the specific surface area measured by the BET method is denoted as S1 (m 2 / g), the specific surface area calculated from the particle size distribution is defined as S2 (m 2 / g), the value of S1 relative to S2 is less than 4.5. DETAILED DESCRIPTION

[0047] Hereinafter, the present invention will be described based on preferred embodiments.

[0048] First, the solid electrolyte pulverization method of the present invention is described. The pulverization method of the present invention is characterized by comprising: a preparation step of preparing a solid electrolyte; and a pulverization step of pulverizing the solid electrolyte, wherein the pulverization step satisfies the relationship shown in the following formula (3).

[0049] D4 / D3<0.49 (3)

[0050] (Wherein, D3 represents the median particle size (μm) of the un-crushed solid electrolyte when there is only one pulverization step. In addition, D3 represents the median particle size (μm) of the solid electrolyte before the pulverization step is performed in any pulverization step when there are two or more pulverization steps.

[0051] D4 represents the median particle size (μm) of the solid electrolyte after the pulverization when there is only one pulverization step. D4 represents the median particle size (μm) of the solid electrolyte immediately after the pulverization step in any of the pulverization steps when there are two or more pulverization steps.

[0052] Hereinafter, the pulverization method of the present invention will be described.

[0053] First, a solid electrolyte is prepared. Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes. Among them, a sulfide solid electrolyte, which is a solid electrolyte containing sulfur (S) element, is preferred.

[0054] The sulfide solid electrolyte may be, for example, a sulfide solid electrolyte containing lithium (Li) element and sulfur (S) element and having lithium ion conductivity, or may be a sulfide solid electrolyte containing lithium (Li) element, phosphorus (P) element and sulfur (S) element and having lithium ion conductivity.

[0055] The sulfide solid electrolyte may be any of crystalline materials, glass ceramics, and glass.

[0056] The sulfide solid electrolyte may have an argyrodite-type crystal structure.

[0057] As sulfide solid electrolytes, for example, Li2S-P2S5, Li2S-P2S5-LiX (X represents one or more halogen elements), Li2S-P2S5-P2O5, Li2S-Li3PO4-P2S5, Li3PS4, Li4P2S6, Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4、Li7P3S 11 , Li3.25 P 0.95 S4, Li a PS b X c (X represents at least one halogen element. a represents a number of 3.0 to 6.0. b represents a number of 3.5 to 4.8. c represents a number of 0.1 to 3.0.)

[0058] In addition, for example, sulfide solid electrolytes described in International Publication No. 2013 / 099834 and International Publication No. 2015 / 001818 can be cited.

[0059] When a sulfide solid electrolyte is used as the solid electrolyte, it is preferred to use a compound of a Li element source, a compound of a P element source, a S element source, and, if necessary, a compound of an X element source as raw materials.

[0060] As the Li element source compound, for example, lithium sulfide (Li 2 S) can be used.

[0061] As the P element source compound, for example, phosphorus pentasulfide (P2S5) can be used.

[0062] As the S element source compound, when the Li element source compound and / or the P element source compound is a sulfide, the sulfide can be used as the S element source compound.

[0063] As the X element source compound, for example, LiX can be used.

[0064] The above raw materials are mixed so that the Li element, the P element, the S element, and the X element as required are in a predetermined molar ratio.

[0065] The mixing is carried out using a jet mill, a ball mill, a rod mill, a vibration ball mill, a planetary mill, a disk mill or the like.

[0066] Next, the mixed raw material composition is calcined in an inert gas atmosphere such as a nitrogen atmosphere, an argon atmosphere, etc. When the raw material composition is a sulfide, the calcination may be performed in a hydrogen sulfide gas atmosphere.

[0067] The calcination temperature is, for example, preferably 300° C. or higher, more preferably 350° C. or higher, and further preferably 400° C. or higher. On the other hand, the calcination temperature is, for example, preferably 700° C. or lower, more preferably 600° C. or lower, and further preferably 550° C. or lower.

[0068] The calcination time is, for example, preferably 0.5 hours or more, more preferably 2 hours or more, and even more preferably 3 hours or more. On the other hand, the calcination time is, for example, preferably 20 hours or less, more preferably 10 hours or less, and even more preferably 5 hours or less.

[0069] By calcining the raw material composition under the above conditions, a solid electrolyte having higher ion conductivity can be easily obtained.

[0070] Next, the roasted product is crushed using a mortar, pestle, ball mill, or the like to obtain a crushed product. Next, preferably, the crushed product is pre-crushed before being subjected to formal crushing to pre-form a solid electrolyte powder of a specified size (median particle size D3). However, when the median particle size of the crushed product and the median particle size of the solid electrolyte powder obtained by pre-crushing satisfy the formula (3) shown below, and also satisfy the formula (4) described later, the pre-crushing can be regarded as the formal crushing and the pre-crushing can be omitted. The "median particle size" in this specification refers to the volume cumulative particle size D at the cumulative volume 50% by volume based on the laser diffraction scattering particle size distribution measurement method. 50 .

[0071] Pre-crushing can be performed by wet or dry methods. Various media mills can be used for pre-crushing. As media mills, ball mills, bead mills, paint mixers, homogenizers, etc. can be used. As the crushing media used in the media mill, balls and beads made of various ceramics headed by aluminum oxide and zirconium oxide are used. The diameter of the crushing media can be set to, for example, 0.1 mm or more and 50 mm or less.

[0072] When the pulverization process is performed by wet method, it is preferred to use an organic solvent as a dispersion medium from the perspective of being able to suppress the generation of hydrogen sulfide gas caused by the reaction between the solid electrolyte and water. As the organic solvent, aromatic organic solvents such as toluene, xylene, benzene and solvent naphtha; and aliphatic organic solvents such as heptane, decane, n-hexane, cyclohexane and mineral spirits can be listed. These organic solvents can be used alone or in combination of two or more.

[0073] Next, the solid electrolyte powder having a median particle size of D3 (μm) obtained by preliminary pulverization is preferably pulverized by wet pulverization (main pulverization) to a median particle size of D4 (μm). This pulverization needs to be performed so as to satisfy the following formula (3).

[0074] D4 / D3<0.49 (3)

[0075] For example, D4 / D3 preferably satisfies the relationship D4 / D3≤0.45, more preferably satisfies the relationship D4 / D3≤0.4, and further preferably satisfies the relationship D4 / D3≤0.3. On the other hand, for example, D4 / D3 preferably satisfies the relationship 0.05≤D4 / D3, more preferably satisfies the relationship 0.1≤D4 / D3, and further preferably satisfies the relationship 0.15≤D4 / D3. Thus, a solid electrolyte powder having excellent ion conductivity can be provided.

[0076] The pulverization process in the formal pulverization can be performed multiple times in a manner that satisfies the above-mentioned pulverization conditions and the pulverization conditions described later by changing the diameter of the pulverization medium, etc. Therefore, D3 represents the median particle size of the unpulverized solid electrolyte when there is only one pulverization process. In addition, D3 represents the median particle size of the solid electrolyte before the pulverization process is performed in any pulverization process when there are two or more pulverization processes. D4 represents the median particle size of the solid electrolyte just after the pulverization is completed when there is only one pulverization process. D4 represents the median particle size of the solid electrolyte just after the pulverization process is performed in any pulverization process when there are two or more pulverization processes.

[0077] When the pulverization time in the pulverization is t (minutes) and the weight of the solid electrolyte powder is m (g), the value t / m of the pulverization time t (minutes) relative to the weight m (g) is preferably greater than 0. On the other hand, t / m is preferably less than 2.3, more preferably 1.5 or less, and further preferably 0.7 or less. Thus, a solid electrolyte powder having better ion conductivity can be provided.

[0078] The main pulverization can be performed so as to satisfy the relationship shown in the following formula (4).

[0079] C / D<3.6×10 -3 (4)

[0080] (where C (S / cm) represents the ionic conductivity σ of the solid electrolyte immediately after the pulverization step when there is only one pulverization step. C1 (S / cm) and the ionic conductivity σ of the un-crushed solid electrolyte C2 (S / cm) difference (σ C1 -σ C2 ). In addition, C (S / cm) represents the ionic conductivity σ of the solid electrolyte before any of the pulverization steps when there are two or more pulverization steps. C3 (S / cm) and the ionic conductivity σ of the solid electrolyte immediately after the arbitrary pulverization step is completed C4 (S / cm) difference (σ C3 -σ C4 ).

[0081] D (μm) represents the median particle size d of the un-crushed solid electrolyte when only one pulverization step is performed. D1 (μm) and the median particle size d of the solid electrolyte immediately after the pulverization step. D2 The difference (d D1 -d D2 ). In addition, D (μm) represents the median particle size d of the solid electrolyte before any of the pulverization steps when there are two or more pulverization steps. D3 (μm) and the median particle size d of the solid electrolyte immediately after the optional pulverization step. D4 The difference (d D3 -d D4 ). )

[0082] In this specification, "ion conductivity" means the value of the ion conductivity measured at 25°C.

[0083] Formula (3) focuses on the median particle size as a direct pulverization condition to limit the conditions for the formal pulverization of the solid electrolyte, while formula (4) focuses not only on the median particle size but also on the ionic conductivity as a target physical property to limit the conditions for the formal pulverization of the solid electrolyte.

[0084] In the formula (4), C / D preferably satisfies, for example, the relationship of 0 ≤ C / D. On the other hand, C / D more preferably satisfies, for example, C / D ≤ 3.0 × 10 -3 The relationship between C / D and D is preferably C / D≤2.5×10 -3 Thus, a solid electrolyte powder having better ion conductivity can be provided.

[0085] The reason why the ionic conductivity of the solid electrolyte powder is improved by adopting the aforementioned pulverization conditions, i.e., formula (3) and formula (4), is that the solid electrolyte powder is finely granulated, thereby increasing the contact area between the solid electrolyte powders, improving the volume conductivity of the ions, and reducing the proportion of fine powder that does not contribute to the volume conductivity, thereby suppressing the increase in the interface of the solid electrolyte powder, which is the cause of the decrease in ionic conductivity.

[0086] From this perspective, the pulverization is preferably performed at 25°C or less, more preferably at 15°C or less, and further preferably at 5°C or less. On the other hand, the pulverization is preferably performed at -15°C or more, more preferably at -10°C or more. Thereby, the aggregation of the solid electrolyte powder can be suppressed, the solid electrolyte powder is finely granulated, and the ionic conductivity caused by the increase in volume conductivity is further improved, and the increase in the interface of the solid electrolyte powder, which is the cause of the decrease in ionic conductivity, can be suppressed. The temperature is the temperature of the refrigerant flowing through the jacket part of the pulverizer.

[0087] The diameter of the pulverizing medium used in the main pulverization is preferably, for example, 0.1 mm or more. On the other hand, the diameter of the pulverizing medium is preferably, for example, 50 mm or less, more preferably 10 mm or less, and further preferably 1.0 mm or less.

[0088] When the wet pulverization is performed, an organic solvent and a solid electrolyte powder are mixed to prepare a slurry, and the slurry is subjected to wet pulverization. From the perspective of successfully obtaining a solid electrolyte powder with high lithium ion conductivity, the concentration of the solid electrolyte powder contained in the slurry is preferably set to 5% by mass or more and 50% by mass or less, for example.

[0089] In wet pulverization using a media mill, the ratio of pulverizing medium to slurry is preferably 5 parts by mass or more and 50 parts by mass or less of pulverizing medium per 100 parts by mass of slurry, from the perspective of easily obtaining a solid electrolyte powder that constitutes a solid electrolyte with high lithium ion conductivity.

[0090] The dispersion time using the media mill is usually 0.1 hours to 60 hours, and is particularly preferably 0.5 hours to 60 hours from the viewpoint of easily obtaining a solid electrolyte powder having high lithium ion conductivity.

[0091] The solid electrolyte powder obtained by the above-mentioned grinding (hereinafter sometimes referred to as "solid electrolyte powder") has a specific surface area measured by the BET method as S1 (m 2 / g), the specific surface area calculated from the particle size distribution is defined as S2 (m 2 / g), the ratio S1 / S2 is less than 4.5.

[0092] The ratio S1 / S2 is, for example, preferably less than 4.2, more preferably less than 3.9, and further preferably less than 3.5. On the other hand, the ratio S1 / S2 may be, for example, greater than 0, may be greater than 0.5, or may be greater than 1.0. The specific surface area S1 measured by the BET method is a physical quantity representing the entire surface area including the main body of the above-mentioned solid electrolyte powder and the fine powder that does not contribute to the ionic conductivity. In contrast, the specific surface area calculated from the particle size distribution is a physical quantity representing the specific surface area of ​​the solid electrolyte powder that does not contain the fine powder. Therefore, a small value of S1 / S2 means that the proportion of fine powder that does not contribute to the ionic conductivity is small. Therefore, for the solid electrolyte powder obtained by the above-mentioned pulverization method, it can also be understood from its physical property values ​​that the volume conductivity is dominant and exhibits high ionic conductivity.

[0093] The cumulative volume particle size D at 90% of the cumulative volume in the solid electrolyte powder based on the laser diffraction scattering particle size distribution measurement method is 90For example, it is preferably less than 40 μm, more preferably 30 μm or less, further preferably less than 5.9 μm, further preferably 5.0 μm or less, and further preferably 4.0 μm or less.

[0094] On the other hand, the volume cumulative particle size D 90 For example, it is preferably 0.7 μm or more, and more preferably 1.0 μm or more.

[0095] By the solid electrolyte powder having such a particle size, the solid electrolyte powders are in close contact with each other, and the volume conductivity becomes dominant, thereby making it possible to provide a solid electrolyte having high ion conductivity.

[0096] Ionic conductivity (S / cm) of solid electrolyte powder relative to median particle size D 50 The ratio of (μm) is preferably greater than 1.3×10 -3 , more preferably 2.0×10 -3 More preferably, 2.5×10 -3 More preferably, 3.0×10 -3 On the other hand, the ionic conductivity (S / cm) relative to the median particle size D 50 The ratio of (μm) is preferably 1.0 or less, and more preferably 0.1 or less. When the solid electrolyte powder satisfies this relationship, high ion conductivity is exhibited.

[0097] Crystallite size of solid electrolyte Relative to the median particle size D of the solid electrolyte powder 50 The ratio of (μm) is preferably 325 or more, more preferably 330 or more, further preferably 400 or more, and further preferably 750 or more. On the other hand, the crystallite size of the solid electrolyte Relative to the median particle size D of the solid electrolyte powder 50 The ratio of (μm) may be, for example, 1200 or less, or 900 or less. Since the crystallite size of the solid electrolyte is larger and the interface of the crystal grains is reduced, the volume conductivity is further improved, and a solid electrolyte powder having high ion conductivity can be provided.

[0098] The solid electrolyte powder of the present invention obtained in this way can be used, for example, as a material constituting a solid electrolyte layer, or as a material contained in an electrode mixture containing an active substance. Specifically, it can be used as a positive electrode mixture constituting a positive electrode layer containing a positive electrode active substance, or as a negative electrode mixture constituting a negative electrode layer containing a negative electrode active substance. Therefore, the solid electrolyte powder of the present invention can be used in a battery having a solid electrolyte layer, i.e., a so-called solid-state battery. More specifically, it can be used in a lithium solid-state battery. A lithium solid-state battery can be a primary battery or a secondary battery, but it is preferably used in a lithium secondary battery. "Solid-state battery" refers to a solid-state battery that does not contain any liquid substance or gel-like substance as an electrolyte, and also includes a method of containing, for example, less than 50% by mass, less than 30% by mass, or less than 10% by mass of a liquid substance or a gel-like substance as an electrolyte.

[0099] The solid electrolyte layer in the solid-state battery can be manufactured by the following methods: for example, a method of dropping a slurry containing the solid electrolyte powder, a binder and a solvent of the present invention onto a substrate and scraping it off with a scraper or the like; a method of cutting with an air knife after the substrate and the slurry are brought into contact; a method of forming a coating film by screen printing or the like, and then removing the solvent by heating and drying, etc. Alternatively, the solid electrolyte powder of the present invention can also be pressed into shape and then appropriately processed for manufacture. In addition to the solid electrolyte powder of the present invention, the solid electrolyte layer may also contain other solid electrolyte powders. The thickness of the solid electrolyte layer in the present invention is typically preferably greater than 5 μm and less than 300 μm, and more preferably greater than 10 μm and less than 100 μm.

[0100] From the perspective of improving lithium ion conductivity, the porosity of the solid electrolyte layer containing the solid electrolyte powder of the present invention is preferably set to 50% or less, preferably 30% or less, and more preferably 20% or less. The porosity of the solid electrolyte layer can be adjusted by, for example, the pressing pressure when the solid electrolyte powder of the present invention is made into a powder compact. The pressing pressure is preferably 20 MPa or more, for example.

[0101] The porosity can be calculated, for example, from the true density and apparent density of the solid electrolyte layer obtained by a liquid phase method (Archimedes method) using the following relational expression.

[0102] Porosity (%) = (true density - apparent density) ÷ true density × 100

[0103] The solid-state battery has a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, and the solid electrolyte layer preferably contains the solid electrolyte of the present invention. As the shape of the solid-state battery, for example, a stacked type, a cylindrical type, and a square type can be listed.

[0104] The positive electrode mixture in the solid-state battery containing the solid electrolyte powder of the present invention includes a positive electrode active material. As the positive electrode active material, for example, a substance used as a positive electrode active material for a lithium secondary battery can be appropriately used. As the positive electrode active material, for example, spinel-type lithium transition metal compounds, lithium metal oxides with a layered structure, etc. can be listed. In addition to the positive electrode active material, the positive electrode mixture may also include other materials headed by a conductive auxiliary agent.

[0105] The negative electrode mixture in the solid-state battery containing the solid electrolyte powder of the present invention contains a negative electrode active material. As the negative electrode active material, for example, a negative electrode mixture used as a negative electrode active material for a lithium secondary battery can be appropriately used. As the negative electrode active material, for example, carbon materials such as lithium metal, artificial graphite, natural graphite and difficult-graphitizable carbon (hard carbon), lithium titanate, titanium-niobium composite oxide, silicon, silicon compounds, tin, and tin compounds can be listed. In addition to the negative electrode active material, the negative electrode mixture may also contain other materials headed by a conductive aid.

[0106] It should be noted that the above is explained through the concept of a solid electrolyte pulverization method, but the present invention can also be applied to a method for pulverizing sulfur compounds that are not limited to solid electrolytes (i.e., regardless of whether they have ion conductivity). As a sulfur compound, any compound containing sulfur (S) element is sufficient, among which, preferably a compound containing at least one of lithium (Li) element, phosphorus (P) element and halogen (X) element. The X element can be set to at least one of fluorine (F) element, chlorine (Cl) element, bromine (Br) element and iodine (I) element. When the present invention is applied to a method for pulverizing sulfur compounds, the above formulas (3) and (4) are represented by the following formulas (1) and (2).

[0107] D2 / D1<0.49 (1)

[0108] (In the formula, D1 represents the median particle size (μm) of the un-crushed sulfur compound when the pulverization method has only one pulverization step. In addition, D1 represents the median particle size (μm) of the sulfur compound before the pulverization step is performed in any pulverization step when the pulverization method has two or more pulverization steps.

[0109] D2 represents the median particle size (μm) of the sulfur compound just after the pulverization when the pulverization method has only one pulverization step. D2 represents the median particle size (μm) of the sulfur compound just after the pulverization step in any of the pulverization steps when the pulverization method has two or more pulverization steps.

[0110] A / B<3.6×10 -3 (2)

[0111] (wherein, A (S / cm) represents the ionic conductivity σ of the sulfur compound immediately after the pulverization step when the pulverization method has only one pulverization step. A1 (S / cm) and the ionic conductivity σ of the uncrushed sulfur compound A2 (S / cm) difference (σ A1 -σ A2 ). In addition, when the pulverization method has two or more pulverization steps, A (S / cm) represents the ionic conductivity σ of the sulfur compound before any pulverization step. A3 (S / cm) and the ionic conductivity σ of the sulfur compound immediately after the optional pulverization step A4 (S / cm) difference (σ A3 -σ A4 ).

[0112] B represents the median particle size d of the un-crushed sulfur compound when the pulverization method has only one pulverization step. B1 (μm) and the median particle size d of the sulfur compound immediately after the pulverization step. B2 The difference (d B1 -d B2 ). In addition, when the pulverization method has two or more pulverization steps, B represents the median particle size d of the sulfur compound before any of the pulverization steps. B3 (μm) and the median particle size d of the sulfur compound immediately after the optional pulverization step. B4 The difference (d B3 -d B4 ). )

[0113] In addition, in the present invention, the above-mentioned solid electrolyte pulverization method can also be applied to a solid electrolyte manufacturing method. The solid electrolyte manufacturing method has the steps of manufacturing a solid electrolyte mother powder using a predetermined raw material and pulverizing the solid electrolyte mother powder. In the manufacturing method, formula (3) and formula (4) in the above-mentioned solid electrolyte pulverization method are represented by the following formula (5) and formula (6).

[0114] D6 / D5<0.49 (5)

[0115] (Wherein, D5 represents the median particle size (μm) of the mother powder when there is only one pulverization step. In addition, D5 represents the median particle size (μm) of the solid electrolyte before the pulverization in any pulverization step when there are two or more pulverization steps.

[0116] D6 represents the median particle size (μm) of the solid electrolyte just after the pulverization when there is only one pulverization step. D6 represents the median particle size (μm) of the solid electrolyte just after the pulverization in any of the pulverization steps when there are two or more pulverization steps.

[0117] E / F<3.6×10 -3 (6)

[0118] (wherein, E (S / cm) represents the ionic conductivity σ of the solid electrolyte immediately after the pulverization step when only one pulverization step is performed. E1 (S / cm) and the ionic conductivity σ of the un-crushed solid electrolyte E2 (S / cm) difference (σ E1 -σ E2 ). In addition, when the pulverization step is performed twice or more, E (S / cm) represents the ionic conductivity σ of the solid electrolyte before any pulverization step. E3 (S / cm) and the ionic conductivity σ of the solid electrolyte immediately after the arbitrary pulverization step is completed E4 (S / cm) difference (σ E3 -σ E4 ).

[0119] F represents the median particle size d of the un-crushed solid electrolyte when the pulverization step is performed only once. F1 (μm) and the median particle size d of the solid electrolyte immediately after the pulverization step. F2 The difference (d F1 -d F2 ). In addition, when the pulverization method has two or more pulverization steps, F represents the median particle size d of the solid electrolyte before any of the pulverization steps. F3 (μm) and the median particle size d of the solid electrolyte immediately after the optional pulverization step. F4 The difference (d F3 -d F4 ). )

[0120] The sulfur compound preferably has lithium ion conductivity. In this specification, lithium ion conductivity refers to the function of being an electrolyte used in lithium ion batteries. As the lithium ion conductivity of the sulfur compound, for example, preferably has a lithium ion conductivity of 4.0 mS / cm or more at room temperature, i.e., 25° C., wherein preferably has a lithium ion conductivity of 4.2 mS / cm or more, particularly preferably has a lithium ion conductivity of 5.0 mS / cm or more, and further preferably has a lithium ion conductivity of 5.5 mS / cm or more and 6.0 mS / cm or more. The lithium ion conductivity can be measured using the method described in the examples described later.

[0121] The present invention includes the following embodiments.

[0122] [1] A method for pulverizing a sulfur compound, the method comprising pulverizing a sulfur compound.

[0123] The method satisfies the relationship shown in the following formula (1).

[0124] D2 / D1<0.49 (1)

[0125] (wherein, D1 represents the median particle size of the un-crushed sulfur compound when the pulverization method has only one pulverization step. In addition, D1 represents the median particle size of the sulfur compound before the pulverization step is performed in any pulverization step when the pulverization method has two or more pulverization steps.

[0126] D2 represents the median particle size of the sulfur compound after the pulverization when the pulverization method has only one pulverization step. D2 represents the median particle size of the sulfur compound after the pulverization step is performed in any of the pulverization steps when the pulverization method has two or more pulverization steps.

[0127] [2] The method for pulverizing a sulfur compound according to [1], wherein, when the pulverization time of the sulfur compound is t (minutes) and the weight of the sulfur compound is m (g), the value of t (minutes) relative to m (g) is greater than 0 and less than 2.3.

[0128] [3] A method for pulverizing a sulfur compound, the method comprising pulverizing a sulfur compound,

[0129] The method satisfies the relationship shown in the following formula (2).

[0130] A / B<3.6×10 -3 (2)

[0131] (Wherein, A (S / cm) represents the difference between the ionic conductivity (S / cm) of the sulfur compound after the pulverization step and the ionic conductivity (S / cm) of the unpulverized sulfur compound when the pulverization method has only one pulverization step. In addition, A (S / cm) represents the difference between the ionic conductivity (S / cm) of the sulfur compound before any pulverization step and the ionic conductivity (S / cm) of the sulfur compound after the arbitrary pulverization step when the pulverization method has two or more pulverization steps.

[0132] When the pulverization method has only one pulverization step, B (μm) represents the difference between the particle size (μm) of the unpulverized sulfur compound and the median particle size (μm) of the sulfur compound after the pulverization step. In addition, when the pulverization method has two or more pulverization steps, B (μm) represents the difference between the median particle size (μm) of the sulfur compound before the arbitrary pulverization step and the median particle size (μm) of the sulfur compound after the arbitrary pulverization step.)

[0133] [4] The method for pulverizing a sulfur compound according to any one of [1] to [3], wherein the sulfur compound has lithium ion conductivity.

[0134] [5] A method for pulverizing a solid electrolyte, comprising:

[0135] a preparation step of preparing a solid electrolyte; and

[0136] a pulverizing step of pulverizing the solid electrolyte,

[0137] The pulverization step satisfies the relationship shown in the following formula (3).

[0138] D4 / D3<0.49 (3)

[0139] (wherein, D3 represents the median particle size of the un-crushed solid electrolyte when there is only one pulverization step. In addition, D3 represents the median particle size of the solid electrolyte before the pulverization step is performed in any pulverization step when there are two or more pulverization steps.

[0140] D4 represents the median particle size of the solid electrolyte after the pulverization when there is only one pulverization step. D4 represents the median particle size of the solid electrolyte after the pulverization step is performed in any of the pulverization steps when there are two or more pulverization steps.

[0141] [6] The solid electrolyte pulverization method according to [5], wherein, when the pulverization time of the solid electrolyte is set to t (minutes), and the weight of the solid electrolyte is set to m (g), the value of t (minutes) relative to the m (g) is greater than 0 and less than 2.3.

[0142] [7] A method for pulverizing a solid electrolyte, comprising:

[0143] a preparation step of preparing a solid electrolyte; and

[0144] a pulverizing step of pulverizing the solid electrolyte,

[0145] The pulverization step satisfies the relationship shown in the following formula (4).

[0146] C / D<3.6×10-3 (4)

[0147] (Wherein, C (S / cm) represents the difference between the ionic conductivity (S / cm) of the solid electrolyte after the pulverization step and the ionic conductivity (S / cm) of the unpulverized solid electrolyte when the pulverization step is performed only once. In addition, C (S / cm) represents the difference between the ionic conductivity (S / cm) of the solid electrolyte before any pulverization step and the ionic conductivity (S / cm) of the solid electrolyte after any pulverization step when the pulverization step is performed twice or more.

[0148] D (μm) indicates the difference between the median particle size (μm) of the un-crushed solid electrolyte and the median particle size (μm) of the solid electrolyte after the crushing step when the crushing method has only one crushing step. In addition, D (μm) indicates the difference between the median particle size (μm) of the solid electrolyte before any crushing step and the median particle size (μm) of the solid electrolyte after the crushing step when the crushing method has two or more crushing steps.)

[0149] [8] The solid electrolyte pulverization method according to any one of [5] to [7], wherein the preparation step includes: a mixing step of mixing raw materials constituting the solid electrolyte to obtain a raw material mixture; and a roasting step of roasting the raw material mixture.

[0150] [9] A method for producing a solid electrolyte, comprising the steps of pulverizing a solid electrolyte mother powder,

[0151] The pulverization step satisfies the relationship shown in the following formula (5).

[0152] D6 / D5<0.49 (5)

[0153] (Wherein, D5 represents the median particle size of the mother powder when there is only one pulverization step. In addition, D5 represents the median particle size of the solid electrolyte before any pulverization step when there are two or more pulverization steps.

[0154] D6 represents the median particle size of the solid electrolyte after the pulverization step when there is only one pulverization step. D6 represents the median particle size of the solid electrolyte after any pulverization step when there are two or more pulverization steps.

[0155]

[10] A method for producing a solid electrolyte according to [9], wherein, when the pulverization time of the pulverization step is set to t (minutes), and the weight of the solid electrolyte is set to m (g), the value of t (minutes) relative to m (g) is greater than 0 and less than 2.3.

[0156]

[11] A method for producing a solid electrolyte, comprising the steps of pulverizing a solid electrolyte mother powder,

[0157] The pulverization step satisfies the relationship shown in the following formula (6).

[0158] E / F<3.6×10 -3 (6)

[0159] (Wherein, E (S / cm) represents the difference between the ionic conductivity (S / cm) of the solid electrolyte after the pulverization step and the ionic conductivity (S / cm) of the unpulverized solid electrolyte when the pulverization step is performed only once. In addition, E (S / cm) represents the difference between the ionic conductivity (S / cm) of the solid electrolyte before any pulverization step and the ionic conductivity (S / cm) of the solid electrolyte after any pulverization step when the pulverization step is performed twice or more.

[0160] F (μm) represents the difference between the median particle size (μm) of the un-crushed solid electrolyte and the median particle size (μm) of the solid electrolyte after the pulverization step when there is only one pulverization step. In addition, F (μm) represents the difference between the median particle size (μm) of the solid electrolyte before any pulverization step and the median particle size (μm) of the solid electrolyte after the pulverization step when there are two or more pulverization steps.)

[0161]

[12] A solid electrolyte, wherein the specific surface area measured by the BET method is denoted as S1 (m 2 / g), the specific surface area calculated from the particle size distribution and true density is defined as S2 (m 2 / g), the value of S1 relative to S2 is less than 4.5.

[0162]

[13] The solid electrolyte according to

[12] , wherein the volume cumulative particle size D at the cumulative volume 90% by volume based on the laser diffraction scattering particle size distribution measurement method is 90 Less than 5.9μm.

[0163]

[14] The solid electrolyte according to

[12] or

[13] , wherein the electrical conductivity (S / cm) is the cumulative particle size D at the cumulative volume 50% by volume based on the laser diffraction scattering particle size distribution measurement method. 50 The value of (μm) is greater than 1.3×10 -3 .

[0164]

[15] The solid electrolyte according to any one of

[12] to

[14] , wherein the crystallite size The cumulative particle size D at 50% by volume relative to the cumulative volume based on the laser diffraction scattering particle size distribution measurement method 50 The value of (μm) is 325 or more.

[0165]

[16] The solid electrolyte according to any one of

[12] to

[15] , wherein the solid electrolyte contains lithium (Li) element, phosphorus (P) element and sulfur (S) element.

[0166] Example

[0167] (Example 1)

[0168] Weigh Li2S powder, P2S5 powder, LiCl powder and LiBr powder so that the composition is Li 5.4 PS 4.4 Cl 0.8 Br 0.8 . These powders are crushed and mixed using a ball mill to obtain a mixed powder. The mixed powder is calcined to obtain a calcined product formed of lithium ion conductive sulfide. The calcination is performed using a tubular electric furnace. During the calcination, 100% pure hydrogen sulfide gas is introduced into the electric furnace at 3.0 L / min. The calcination temperature is set to 490°C and the calcination is performed for 4 hours. The results of the XRD measurement confirm that the calcined product has a crystal phase of a argyrodite-type crystal structure.

[0169] The calcined product was pre-crushed by a general method to obtain a median particle size D 50 A solid electrolyte of about 3 μm is prepared, and the crushed material is then mixed with an organic solvent to form a slurry with a concentration of 15% by mass. The slurry is supplied to a bead mill device ("First Mil" manufactured by Ashizawa Finetech Ltd.) for wet crushing (formal crushing). The beads used in the bead mill device are made of alumina with a diameter of 0.2 mm, and a refrigerant at 0°C is passed into the jacket of the device. In addition, toluene is used as an organic solvent. Relative to 100 parts by mass of the slurry, 31 parts by mass of beads are used for wet crushing for 10 minutes. At this time, the ratio D2 / D1 of the median particle size D1 of the pre-crushed solid electrolyte powder to the median particle size D2 of the formally crushed solid electrolyte powder is set to 0.27, and the crushing time (t / m) per 1 g is set to 0.67 min / g.

[0170] After wet pulverization, the slurry is separated into solid and liquid, and the solid component is dried. The dried calcined product is sieved with a sieve with an aperture of 53 μm to obtain the target solid electrolyte powder. In addition, other conditions such as energy are appropriately selected according to the target solid electrolyte powder.

[0171] Table 1 shows other properties.

[0172] The median particle size D of the solid electrolyte powder was measured under the following conditions: 50 and particle size D 90 , specific surface area, crystallite size, ionic conductivity and particle size changes.

[0173] <Median particle size D 50 and D 90 >

[0174] The sample (powder) was placed in an organic solvent using an automatic sampler for a laser diffraction particle size distribution measuring device (Microtrac SDC manufactured by Microtrac BEL), and irradiated with 30 W ultrasonic waves for 60 seconds at a flow rate of 50% multiple times. The particle size distribution was measured using a laser diffraction particle size distribution measuring machine "MT3000II" manufactured by Microtrac BEL, and D was measured from the obtained volume-based particle size distribution graph. 50 and D 90 Toluene was used as the organic solvent.

[0175] The measurement of the particle size distribution of the solid electrolyte using the laser diffraction scattering particle size distribution measurement method is carried out by the following steps. Using an automatic sampler for the laser diffraction particle size distribution measurement device ("Microtorac SDC" manufactured by MicrotracBEL), the flow rate of the measurement sample containing the solid electrolyte is set to 50%, and the measurement sample containing the solid electrolyte is irradiated with 30W ultrasonic waves for 60 seconds. Then, the particle size distribution is measured using a laser diffraction particle size distribution measurement machine "MT3000II" manufactured by MicrotracBEL, and the particle size when the cumulative volume is 50% by volume and 90% by volume is obtained from the obtained volume-based particle size distribution diagram, which are respectively taken as D 50 and D 90 It should be noted that the determination of D 50 and D 90 When the organic solvent is passed through a 60 μm filter, the solvent refractive index is set to 1.50, the particle permeability condition is set to "transmittance", the particle refractive index is set to 1.59, the shape is set to "non-spherical", the measurement range is set to 0.133 μm to 704.0 μm, the measurement time is set to 10 seconds, and the measurement is performed twice. The average values ​​of the obtained measurement values ​​are respectively taken as D 50 and D 90 .

[0176] A sample for measurement containing a solid electrolyte was prepared as follows. First, a slurry containing a solid electrolyte was prepared by manually mixing 0.3 g of a solid electrolyte and 5.7 g of a liquid containing a dispersant (mass of toluene:mass of dispersant (SN Dispersant 9228 manufactured by SAN NOPCO Ltd.) = 19:1 (mass ratio)). Next, a sample for measurement containing a solid electrolyte was prepared by pouring 6 ml of the slurry containing a solid electrolyte into an organic solvent (toluene).

[0177] D of the raw material powder of the solid electrolyte 50 and D 90 The measurement is carried out in the same manner as above except that a measurement sample containing raw material powder is used. The measurement sample containing raw material powder is prepared as follows. First, as described later, a slurry containing raw material powder (raw material slurry) is prepared. Next, a few drops of a dispersant (SN Dispersant 9228 manufactured by SAN NOPCO Ltd.) are added dropwise to an organic solvent (toluene), and then a few drops of the slurry containing raw material powder are added dropwise to prepare a measurement sample containing raw material powder.

[0178] <Specific surface area>

[0179] [Measurement of BET specific surface area]

[0180] The sample (powder) was vacuum heated at 120°C for 1 hour using a pretreatment device called "BELPREP-vacII" manufactured by MicrotracBEL. Then, a specific surface area measuring device called "BELSORP-miniII" manufactured by MicrotracBEL was used to calculate the specific surface area from the amount of nitrogen adsorbed at liquid nitrogen temperature (77K) using the BET (Brunauer-Emmett-Teller) method. Pretreatment was performed at 120°C for more than 30 minutes under a reduced pressure environment. He was used as the purge gas and N2 was used as the adsorbent. The specific surface area measured by the BET method was taken as S1 (m 2 / g).

[0181] 〔Specific surface area calculated from particle size distribution and true density〕

[0182] (CS value)

[0183] For a certain powder, the CS value of the powder is the surface area per unit volume of the powder assuming that the shape of the particles constituting the powder is spherical, and the unit is m 2 / cm 3 The CS value of a powder is given by the following formula based on the volume-based particle size distribution of the powder measured by a laser diffraction scattering particle size distribution measurement method: CS value (m 2 / cm3 )=6 / MA. It should be noted that MA is the area average particle size (μm), which is obtained by the following formula: MA(μm)=ΣVi / Σ(Vi / di) [where Vi is the frequency and di is the median of the particle size classification. ] The CS value is determined by comparing it with D 50 and D 90 In the same manner as the measurement of , the particle size distribution was measured using a laser diffraction particle size distribution measuring apparatus "MT3000II" manufactured by Microtrac BEL, and the CS value was calculated from the obtained volume-based particle size distribution graph.

[0184] (True density)

[0185] The true density was calculated by gas replacement using the true density evaluation device "BELPycno" manufactured by Microtrac BEL. Pretreatment was performed by purging 5 times. Alumina with a 10cc hole was used for measurement, and the sample was filled to about 70% of the hole. The unit of true density thus obtained is g / cm 3 .

[0186] <S2=X / Y>

[0187] For a certain powder, based on the following formula:

[0188] S2=X / Y

[0189] [Wherein, X represents the true density of the powder (g / cm 3 ), Y represents the CS value of the powder (m 2 / cm 3 The calculated value is the CS value (m) obtained by assuming that the particles are spherical based on the particle size distribution measurement. 2 / cm 3 )Except true density (g / cm 3 ) is used as the specific surface area S2 (m 2 / g).

[0190] <Crystalline Size>

[0191] The measurement was performed without exposure to the atmosphere using a powder X-ray diffraction apparatus "SmartLab SE" manufactured by Rigaku Co., Ltd. The measurement conditions are as follows.

[0192] Tube voltage: 40kV

[0193] Tube current: 50mA

[0194] ·X-ray: Cu Kα ray (including CuKα1 ray and CuKα2 ray at an intensity ratio of 2:1) ·Optical system: Focused beam method

[0195] Detector: One-dimensional detector

[0196] ·Measurement well range: 2θ=10-120°

[0197] Step length: 0.02°

[0198] Scanning speed: 1° / min

[0199] In addition, SRM660c (compound name: LaB6) manufactured by NIST (National Institute of Standards and Technology) was measured under the same conditions and used as a width standard, and SRM640f (compound name: Si) was measured under the same conditions and used as an angle standard.

[0200] The analysis was performed using SmartLab Studio II of Rigaku Co., Ltd. The analysis steps are as follows. First, identification was performed. The following CIF file (crystal information file) was read and the substance was determined. The CIF file was obtained from ICSD (inorganic crystal structure database). In the analysis of sulfide solid electrolytes, the ICSD collection code used 418488. Next, Rietveld analysis was performed using WPPF. As a width correction, a width standard data file was selected. This file corresponds to a file in which the XRD data obtained by measuring SRM660c was identified using LaB6, and analyzed and saved by a method similar to the method shown below. In addition, as an angle correction, an angle standard data file is selected. This file corresponds to a file in which the XRD data obtained by measuring SRM640f was identified with Si, and analyzed and saved by a method similar to the method shown below. The angle and width of the peak are corrected using an external standard sample. Use the "split-type pseudo-Voigt function" as the model function for the peak shape. Next, select "Fine parameter setting"-"method" from the "Basic" tab, and then select "Rietveld / dl mode".

[0201] Next, refinement is performed. During refinement, various parameters are adjusted until sufficient convergence is achieved. For example, in the case of S value, it is generally less than 1.5. The analyzed crystallite size is obtained from "Display" - "Analysis Results".

[0202] <Ionic conductivity>

[0203] The solid electrolyte powders obtained in Examples and Comparative Examples were placed in a glove box purged with sufficiently dry Ar gas (dew point -60°C or less) and subjected to a pressure of about 6 t / cm 2The lithium ion conductivity was measured by uniaxial pressing under a load of 10 mm and a pellet having a thickness of about 1 mm to 8 mm. The lithium ion conductivity was measured using a Solartron 1255B electrochemical measurement system (1280C) and an impedance / gain phase analyzer (SI 1260) manufactured by Solartron Analytical. The measurement conditions were set to an AC impedance method with a temperature of 25°C, a frequency of 100 Hz to 1 MHz, and an amplitude of 100 mV.

[0204] <Particle size change>

[0205] When there is only one pulverization step, the particle size d of the unpulverized sulfur compound is calculated as B1 (μm) and the particle size d of the sulfur compound after the pulverization step B2 The difference (d B1 -d B2 In addition, when the pulverization method has two or more pulverization steps, the particle size d of the sulfur compound before any of the pulverization steps is calculated. B3 (μm) and the particle size d of the sulfur compound immediately after the optional pulverization step. B4 The difference (d B3 -d B4 )(μm).

[0206] (Example 2)

[0207] The solid electrolyte powder was obtained in the same manner as in Example 1 except that the bead diameter was set to 0.5 mm, the pulverization time of the main pulverization was set to 35 minutes, the ratio D2 / D1 of the median particle size D1 of the solid electrolyte powder after the preliminary pulverization to the median particle size D2 of the solid electrolyte powder after the main pulverization was set to 0.37, and the pulverization time (t / m) per 1 g was set to 2.3 min / g. The results are shown in Table 1.

[0208] (Comparative Example 1)

[0209] The bead diameter was set to 0.3 mm, the pulverization time of the main pulverization was set to 35 minutes, a refrigerant at 10° C. was passed through the jacket of the bead mill device, the ratio D2 / D1 of the median particle size D1 of the solid electrolyte powder after the preliminary pulverization to the median particle size D2 of the solid electrolyte powder after the main pulverization was set to 0.49, and the pulverization time (t / m) per 1 g was set to 2.3 min / g, and a solid electrolyte powder was obtained in the same manner as in Example 1. The results are shown in Table 1.

[0210] [Table 1]

[0211]

[0212] According to the examples, since the above equations (1) and (2) are satisfied, and further equations (3) and (4) are satisfied, the ionic conductivity of the solid electrolyte obtained by pulverization (specifically, the ionic conductivity (S / cm) relative to the volume cumulative particle size D) is 50 (μm) value (ionic conductivity / D 50 )) is higher than 1.3×10 -3 On the other hand, in the comparative example which does not satisfy the above formula (1) and formula (2), and further does not satisfy the formula (3) and formula (4), it can be seen that (ion conductivity / D 50 ) is 1.3×10 -3 , compared with the embodiment, the value becomes lower.

[0213] Industrial Applicability

[0214] According to the present invention, a solid electrolyte powder constituting a solid electrolyte having excellent ion conductivity can be provided.

Claims

1. A method for pulverizing a sulfur compound, which is a method for pulverizing a sulfur compound. The method satisfies the relationship shown in the following formula (1): D2 / D1<0.49 (1) In formula (1), D1 represents the median particle size of the un-crushed sulfur compound when the pulverization method has only one pulverization step. In addition, D1 represents the median particle size of the sulfur compound before the pulverization step is performed in any pulverization step when the pulverization method has two or more pulverization steps. D2 represents the median particle size of the sulfur compound after pulverization when the pulverization method has only one pulverization step, and D2 represents the median particle size of the sulfur compound after the pulverization step is performed in any of the pulverization steps when the pulverization method has two or more pulverization steps.

2. The method for pulverizing a sulfur compound according to claim 1, wherein: When the pulverization time of the sulfur compound is t (minutes) and the weight of the sulfur compound is m (g), the value of t (minutes) relative to the m (g) is greater than 0 and less than 2.

3.

3. A method for pulverizing a sulfur compound, which is a method for pulverizing a sulfur compound. The method satisfies the relationship shown in the following formula (2): A / B<3.6×10 -3 (2) In formula (2), A (S / cm) represents the difference between the ionic conductivity (S / cm) of the sulfur compound after the pulverization step and the ionic conductivity (S / cm) of the unpulverized sulfur compound when the pulverization method has only one pulverization step. In addition, A (S / cm) represents the difference between the ionic conductivity (S / cm) of the sulfur compound before any pulverization step and the ionic conductivity (S / cm) of the sulfur compound after the arbitrary pulverization step when the pulverization method has two or more pulverization steps. When the pulverization method has only one pulverization step, B (μm) represents the difference between the particle size (μm) of the unpulverized sulfur compound and the median particle size (μm) of the sulfur compound after the pulverization step. In addition, when the pulverization method has two or more pulverization steps, B (μm) represents the difference between the median particle size (μm) of the sulfur compound before any pulverization step and the median particle size (μm) of the sulfur compound after the arbitrary pulverization step.

4. The method for pulverizing a sulfur compound according to any one of claims 1 to 3, wherein The sulfur compound has lithium ion conductivity.

5. A method for pulverizing a solid electrolyte, comprising: a preparation step of preparing a solid electrolyte; and a pulverizing step of pulverizing the solid electrolyte, The pulverization process satisfies the relationship shown in the following formula (3): D4 / D3<0.49 (3) In formula (3), D3 represents the median particle size of the un-crushed solid electrolyte when there is only one pulverization step, and D3 represents the median particle size of the solid electrolyte before the pulverization step is performed in any pulverization step when there are two or more pulverization steps. D4 represents the median particle size of the solid electrolyte after pulverization when the pulverization step is performed only once, and represents the median particle size of the solid electrolyte after the pulverization step is performed in any of the pulverization steps when the pulverization step is performed twice or more.

6. The solid electrolyte pulverization method according to claim 5, wherein: When the pulverization time of the solid electrolyte is t (minutes) and the weight of the solid electrolyte is m (g), the value of t (minutes) relative to m (g) is greater than 0 and less than 2.

3.

7. A method for pulverizing a solid electrolyte, comprising: a preparation step of preparing a solid electrolyte; and a pulverizing step of pulverizing the solid electrolyte, The pulverization step satisfies the relationship shown in the following formula (4): C / D<3.6×10 -3 (4) In formula (4), C (S / cm) represents the difference between the ionic conductivity (S / cm) of the solid electrolyte after the pulverization step and the ionic conductivity (S / cm) of the unpulverized solid electrolyte when the pulverization step is performed only once. In addition, C (S / cm) represents the difference between the ionic conductivity (S / cm) of the solid electrolyte before any pulverization step and the ionic conductivity (S / cm) of the solid electrolyte after any pulverization step when the pulverization step is performed twice or more. D (μm) represents the difference between the median particle size (μm) of the uncrushed solid electrolyte and the median particle size (μm) of the solid electrolyte after the crushing step when the crushing method has only one crushing step. In addition, D (μm) represents the difference between the median particle size (μm) of the solid electrolyte before any crushing step and the median particle size (μm) of the solid electrolyte after the arbitrary crushing step when the crushing method has two or more crushing steps.

8. The method for pulverizing a solid electrolyte according to any one of claims 5 to 7, wherein: The preparation step includes: a mixing step of mixing raw materials constituting the solid electrolyte to obtain a raw material mixture; and a baking step of baking the raw material mixture.

9. A method for producing a solid electrolyte, comprising the steps of pulverizing a solid electrolyte mother powder, The pulverization process satisfies the relationship shown in the following formula (5): D6 / D5<0.49 (5) In formula (5), D5 represents the median particle size of the mother powder when there is only one pulverization step, and D5 represents the median particle size of the solid electrolyte before any pulverization step when there are two or more pulverization steps. When the pulverization step is performed only once, D6 represents the median particle size of the solid electrolyte after the pulverization step. When the pulverization step is performed twice or more, D6 represents the median particle size of the solid electrolyte after any of the pulverization steps.

10. The method for producing a solid electrolyte according to claim 9, wherein: When the pulverization time in the pulverization step is t (minutes) and the weight of the solid electrolyte is m (g), the value of t (minutes) relative to m (g) is greater than 0 and less than 2.

3.

11. A method for producing a solid electrolyte, comprising the steps of pulverizing a solid electrolyte mother powder, The pulverization step satisfies the relationship shown in the following formula (6): E / F<3.6×10 -3 (6) In formula (6), E (S / cm) represents the difference between the ionic conductivity (S / cm) of the solid electrolyte after the pulverization step and the ionic conductivity (S / cm) of the unpulverized solid electrolyte when the pulverization step is performed only once. In addition, E (S / cm) represents the difference between the ionic conductivity (S / cm) of the solid electrolyte before any pulverization step and the ionic conductivity (S / cm) of the solid electrolyte after any pulverization step when the pulverization step is performed twice or more. When the pulverizing step is performed only once, F(μm) represents the difference between the median particle size (μm) of the unpulverized solid electrolyte and the median particle size (μm) of the solid electrolyte after the pulverizing step. In addition, when the pulverizing step is performed twice or more, F(μm) represents the difference between the median particle size (μm) of the solid electrolyte before any pulverizing step and the median particle size (μm) of the solid electrolyte after the any pulverizing step.

12. A solid electrolyte, wherein: The specific surface area measured by the BET method is defined as S1 (m 2 / g), the specific surface area calculated from the particle size distribution and true density is defined as S2 (m 2 / g), the value of S1 relative to S2 is less than 4.

5.

13. The solid electrolyte according to claim 12, wherein The cumulative volume particle size D at 90% of the cumulative volume based on the laser diffraction scattering particle size distribution measurement method 90 Less than 40μm.

14. The solid electrolyte according to claim 12 or 13, wherein Ion conductivity (S / cm) relative to the cumulative volume 50% by volume based on the laser diffraction scattering particle size distribution measurement method. 50 The value of (μm) is greater than 1.3×10 -3 .

15. The solid electrolyte according to claim 12 or 13, wherein Crystallite size The cumulative particle size D at 50% by volume relative to the cumulative volume based on the laser diffraction scattering particle size distribution measurement method 50 The value of (μm) is 325 or more.

16. The solid electrolyte according to claim 12 or 13, wherein The solid electrolyte includes lithium (Li) element, phosphorus (P) element, and sulfur (S) element.

Citation Information

Patent Citations

  • Solid electrolyte microparticle and its manufacturing method

    JP2008004459A

  • Solid electrolyte and its manufacturing method

    JP2009211950A

  • Apparatus and method for manufacturing solid electrolyte

    JP2010140893A

  • Sulfide-type solid electrolyte

    WO2013099834A1

  • Crystalline solid electrolyte and production method therefor

    WO2015001818A1